The feminist reference desk : concepts, critiques, and conversations - Accardi, Maria T. (Sacremento : Library Juice Press, 2017)
"This edited collection considers how feminist strategies and philosophies might initiate, reshape, and critique approaches to library reference services"--
Female articulation and the librarian (or, so hard to say) / Michelle Reale -- Part I. Emotional work and ethics of care -- Behavioral expectations for the mommy librarian : the successful reference transaction as emotional labor / Celia Emmelhainz, Erin Pappas, and Maura Seale -- Nothing more than a gear in your car : neutrality and feminist reference in the academic library / Nina Clements -- Purposeful and productive care : the feminist ethic of care and the reference desk / Sara Howard -- Feminist reference services : transforming relationships through an ethic of care / Sharon Ladenson -- A woman's work is never done : reference outside the library / Kelly McElroy -- Part II. Ways of doing and rethinking the work -- Seeing writing center practices through a feminist lens & applying the lessons learned to reference desk practice / Dory Cochran -- Margaret Fuller's legacy interpreted for the postmodern library / Mellissa J. Hinton -- Proceed with care : reviewing reference services through the feminist lens / Elizabeth Hoppe and Karen Jung -- Feminist pedagogy and special collections reference : shifting the balance / Melanie J. Meyers -- Filling in the gaps : using zines to amplify the voices of people who are silenced in academic research / Dawn Stahura -- Information of my own : peer reference and feminist pedagogy / Lauren Wallis -- Social justice in the stacks : opening the borders of feminism in libraries / Gina Watts -- Part III. Intersectional and collaborative work -- Intersectionality at the reference desk : lived experiences of women of color librarians / Rose L. Chou and Annie Pho -- Reference and beyond : aspiring librarians and intersectional feminist strategies / Nicole A. Cooke, Jennifer Margolis Jacobs, Katrina Spencer, Chloe Collins, and Rebekah Loyd -- Feminist pedagogy and the critical catalog / Katherine Crowe and Erin Elzi -- Feminist LibGuides : towards inclusive practices in guide creation, use, and reference interactions / Amanda Meeks -- Exploring a feminist disability studies reference desk / Brian A. Sullivan and Malia Willey -- LIS graduate student workers, feminist pedagogy, and the reference desk : praxis and a narrative / Raina Bloom -- Feminist pedagogy and the reference desk : a conversation / Jeremy McGinniss and Angela Pashia -- The creature questions its reflection : lyrical feminist explorations of reference desk interactions / Corinne Gilroy and Alexandrina Hanam.
Includes bibliographical references and index.
Keywords: Reference services (Libraries) -- Philosophy; Academic libraries -- Reference services -- Philosophy; Research -- Methodology -- Study and teaching; Information literacy -- Study and teaching; Librarians -- Professional ethics; Feminist ethics; Critical pedagogy; Feminism and higher education